1983
DOI: 10.1161/01.cir.67.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Echoventriculography -- a simultaneous analysis of two-dimensional echocardiography and cineventriculography.

Abstract: SUMMARY Two-dimensional echocardiography underestimates left ventricular volume compared with cineventriculography. To exclude the influence of difference in heart rate, blood pressure, respiration phases and any effect of the contrast material on left ventricular function, simultaneous studies of twodimensional echocardiography and cineventriculography-echoventriculography were performed in 46 patients. Apical two-dimensional echocardiograms in the right anterior oblique (RAO) equivalent view were recorded be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(59 citation statements)
references
References 24 publications
1
54
1
3
Order By: Relevance
“…A limitation of our technique is that LV volume measurements obtained by apical imaging are known to be underestimated because of the inadvertent use of tangential scan planes, 35 especially in the presence of anterior and apical wall motion abnormalities. 36 Although recent studies have demonstrated the advantages of 3D imaging in this context, this issue requires further investigation.…”
Section: Limitationsmentioning
confidence: 99%
“…A limitation of our technique is that LV volume measurements obtained by apical imaging are known to be underestimated because of the inadvertent use of tangential scan planes, 35 especially in the presence of anterior and apical wall motion abnormalities. 36 Although recent studies have demonstrated the advantages of 3D imaging in this context, this issue requires further investigation.…”
Section: Limitationsmentioning
confidence: 99%
“…18 With RT3DE, the 2-dimensional cutting plane can be positioned after acquisition, allowing it to be placed at the exact center of the LVOT or the left ventricle; measurements, such as thickness of the ventricular septum and diameter of the aorta, can be made with greater confidence. In the present study, we showed that the thickness of the ventricular septum in patients with HC was significantly larger than in controls, and it significantly decreased after myectomy.…”
Section: Eft Ventricular Outflow Tract (Lvot) Obstruction Ismentioning
confidence: 99%
“…In the human heart the most potent pharmacologic agents in this regard are catecholamines that possess f3-adrenergic agonist activity (6), and both intravenous (7)(8)(9)(10)(11) and orally effective (12,13) f3-agonists have been used in the treatment of heart failure.…”
mentioning
confidence: 99%